2016
DOI: 10.1021/acs.est.6b03602
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biotransformation Rates of Organic Chemicals in Fish: Relationship with Bioconcentration and Biomagnification Factors

Abstract: In vivo dietary bioaccumulation experiments for 85 hydrophobic organic substances were conducted to derive the in vivo gastrointestinal biotransformation rates, somatic biotransformation rates, bioconcentration factors (BCF), and biomagnification factors (BMF) for improving methods for bioaccumulation assessment and to develop an in vivo biotransformation rate database for QSAR development and in vitro to in vivo biotransformation rate extrapolation. The capacity of chemicals to be biotransformed in fish was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 29 publications
4
42
0
Order By: Relevance
“…More recently, Lo et al [14] investigated the relationship between BCF and BMF using 85 hydrophobic organic substances. More recently, Lo et al [14] investigated the relationship between BCF and BMF using 85 hydrophobic organic substances.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, Lo et al [14] investigated the relationship between BCF and BMF using 85 hydrophobic organic substances. More recently, Lo et al [14] investigated the relationship between BCF and BMF using 85 hydrophobic organic substances.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these equations, the BMF kg of a chemical with a BCF L of 5000 would be 0.11 with a 95% CI of 0.040 to 0.28, and the 5% lipid-normalized BMF kg of a chemical with a BCF L of 5000 would be 0.10 with a 95% CI of 0.036 to 0.28. More recently, Lo et al [14] investigated the relationship between BCF and BMF using 85 hydrophobic organic substances. They found that for substances not biotransformed or transformed exclusively in the body of the fish, the BCF and BMF appeared to be closely correlated.…”
Section: Bmf Kg Hcbmentioning
confidence: 99%
See 3 more Smart Citations